The Effects of Protein-Energy Malnutrition On Children Under Five Years of Age - Muhammad Zubair; Meenakshi Mishra; Umesh Kumar; Pankaj Kishor Mishra (International Journal of Pharma and Bio Sciences, 2024)
Nutritive status is one of the essential pointers for crucial signs of health. Malnutrition is a public health problem of significant significance in growing countries. Malnutrition affects about one in five children and is associated with a higher risk of inflammation and other diseases. This review identifies several protein-energy malnutrition (PEM) types and presents our perspective on PEM. This review outlines the diseases caused by PEM and the variables influenced by PEM. Additionally, it describes how children are fed in India. The term "severe acute malnutrition" has replaced the term PEM, which was once used to describe children with severe wasting and kwashiorkor (nutritional edema). The determinants of PEM can be broadly divided into four groups: biological, environmental, behavioural, and healthcare service-related factors. This article reviews malnutrition health status in developing countries, its classifications, determinants, epidemiology and impact, biochemical disturbances in the body, laboratory investigation, diseases, effects on the brain, and influence of climate change.